2023
DOI: 10.1021/acs.inorgchem.3c01041
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Protein Interaction in the Speciation of Potential VIVO–Pyridinone Drugs

Abstract: Vanadium complexes (VCs) are promising agents for the treatment, among others, of diabetes and cancer. The development of vanadium-based drugs is mainly limited by a scarce knowledge of the active species in the target organs, which is often determined by the interaction of VCs with biological macromolecules like proteins. Here, we have studied the binding of [VIVO(empp)2] (where Hempp is 1-methyl-2-ethyl-3-hydroxy-4(1H)-pyridinone), an antidiabetic and anticancer VC, with the model protein hen egg white lysoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…Structure C, obtained at a pH of 7.5, contains a similar [V IV O(empp) 2 (H 2 O)] adduct, but a second [V IV O(empp) 2 (H 2 O) 2 ] + adduct is also found to be H-bonded to the side chain of Arg125. Altogether, supported by ESI-MS and EPR data, these results emphasize the speciation of [V IV OL 2 ] compounds upon protein interactions and the possible binding of different V-fragments, which is important to better understanding their transport in the bloodstream and possible binding to proteins inside cells [ 133 ].…”
Section: Vanadium-containing Proteins and X-ray Crystallographymentioning
confidence: 75%
See 1 more Smart Citation
“…Structure C, obtained at a pH of 7.5, contains a similar [V IV O(empp) 2 (H 2 O)] adduct, but a second [V IV O(empp) 2 (H 2 O) 2 ] + adduct is also found to be H-bonded to the side chain of Arg125. Altogether, supported by ESI-MS and EPR data, these results emphasize the speciation of [V IV OL 2 ] compounds upon protein interactions and the possible binding of different V-fragments, which is important to better understanding their transport in the bloodstream and possible binding to proteins inside cells [ 133 ].…”
Section: Vanadium-containing Proteins and X-ray Crystallographymentioning
confidence: 75%
“…In the last years, some SC-XRD studies of oxidovanadium(IV and V) complexes bound to proteins have been reported, namely involving the V IV O 2+ center. The first SC-XRD structure involving the oxidovanadium(IV) ion was reported in 2014 [ 104 ] and a few others have been reported since 2021 [ 16 , 75 , 132 , 133 , 134 ]. Table 4 summarizes the six VCs’ organic ligands bound to three different model proteins (lysozyme, RNase and trypsin) in the PDB, published since 2015, which will be discussed in the next sections.…”
Section: Vanadium-containing Proteins and X-ray Crystallographymentioning
confidence: 99%
“…Although the understanding of the POVs binding to proteins is a crucial step for elucidating the mechanism of biological action of these compounds, this research field, due to its high complexity, has been scarcely investigated [14,15] . In our continuous efforts to characterize the interaction of proteins with metal complexes, [16–19] we have recently studied the structures of the adducts formed upon reaction of proteins with V IV OL 2 compounds, where L − is a monoanionic bidentate organic ligand [20–22] . Crystallography works reporting the structures of these adducts are rare [20–24] and the few studies carried out on these systems revealed binding preference of V containing fragments, in particular V IV OL + and V IV OL 2 , for Asn, Asp, Glu and His side chains.…”
Section: Figurementioning
confidence: 99%
“…[3][4][5][6] Non-innocent Schiff base V-catecholates have interesting electronic properties with the potential for redox taking place not only on the metal center but also on the ligand. 3,[7][8][9] The subclass of non-innocent Schiff base V-catecholates have recently been discovered to have desirable pharmaceutical properties [3][4][5][6][8][9][10][11][12][13][14][15][16] which expanded the known anti-diabetic and anti-cancer properties of vanadium complexes. 3,4,6,[8][9][10][11][12][13][14][15][16][17][18] The reported antiproliferative properties of the class of non-innocent Schiff base V-catecholates were reported to surpass the efficacy of cisplatin against in human chondrosarcoma (SW1353) bone cells, T98G glioblastoma cells, aggressive mesenchymal-like MDA-MB-231 cells, A549 (lung), and PANC-1 (pancreas) cancer cell lines, and HFF-1 (human foreskin fibroblasts) normal cells.…”
Section: Introductionmentioning
confidence: 99%